Influence of Carbon Addition to Fe-Mn-Si Type Alloy on the Structure and Shape Memory Effect - Witold Prendota; Kamil Goc; Shunsuke Miyazawa; Akito Takasaki; Damian Rybicki; Czeslaw Kapusta (Advances in Materials Science and Engineering)
The study presented is focused on the influence of carbon addition on properties of the Fe-Mn-Si type intelligent materials with basic composition of Fe64Mn30Si6 (wt. %). Three alloys were prepared, starting from elemental powders, with 0, 0.1, and 0.3 wt. % of carbon, at corresponding silicon content reduction. For the synthesis, the mechanical alloying, sintering, and annealing were applied. Further process involved deformation and subsequent heating in a furnace. High temperature X-ray diffraction patterns, obtained at room temperature and up to 600°C, showed evolution of α′, γ, and ε phase peaks. The study revealed that a small carbon addition (of 0.1 wt. %), could increase shape recovery stress, even up to 1.8% after one cycle of training. The higher carbon content leads to a deterioration of the property. Also, relative density differences are observed between the sintered Fe64Mn30Si6 (wt. %) alloys with before/after annealing with/without mechanical alloying involvement.